JESUS AND HIS APOSTLES AS PROPHETS PAR EXCELLENCE IN LUKE-ACTS - Moon, Sewon (Scriptura, 2013)
In Luke-Acts, Jesus and his Apostles are characterized by language that is reminiscent of the Old Testament prophets, particularly Moses and Elijah. This article atttempts to understand the meaning of such characterization in the narrative world of Luke-Acts. This world includes the frameworks of Judaism of the first century as a hierocratic symbolic empire, the perception of the prophet par excellence like Moses in Judaism, and the plot and geographical movement of Luke-Acts. This article argues that the earthly Jesus (Lk. 4:16-30) and the Twelve Apostles after the Pentecost (Acts 2) are characterized in Luke-Acts as prophets par excellence who confront the current hierocratic symbolic empire, participating in the making and renewal of the Covenant, which underlies the identity of God’s people.